Mitigating high ‘equity capital’ risk exposure to ‘small cap’ sector in India: analysing ‘key factors of success’ for ‘Institutional Investors’ whilst Investing in small cap sector in India - Narang, Anish (2014)
This paper deals with the subject of mitigating high ‘Equity Capital’ Risk Exposure to ‘Small Cap’ Sector in India. Institutional investors in India are prone to be risk averse when it comes to investing in the small cap sector in India as they find the companies risky and volatile. This paper will help analyse ‘Key Factors of success’ for ‘Institutional Investors’ whilst investing in Small Cap sector in India as some of these Indian small cap stocks offer handsome returns despite economic downturn. This paper has been harnessed carefully under the influence of expert investors, which includes Benjamin Graham (Security Analysis); Warren Buffet; Philip Fisher (Common Stocks and Uncommon Profits); and Aswath Damodaran.